2023
DOI: 10.3390/logistics7020027
|View full text |Cite
|
Sign up to set email alerts
|

Logistics and Supply Chain Resilience of Japanese Companies: Perspectives from Impacts of the COVID-19 Pandemic

Abstract: Background: Enhancing the resilience of global supply chains has become of increasing priority in response to recent natural disasters and the COVID-19 pandemic. Methods: This paper presents findings from semi-structured interviews with five Japanese companies conducted between November 2020 and February 2021 to examine the impacts of the COVID-19 pandemic on different aspects of logistics and supply chain activities and resilience strategies implemented. The interviews focused on firms’ financial performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…During the execution of the algorithm, the two rates, α (n) and η (n) , are adjusted according to Formulas (6) and (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the execution of the algorithm, the two rates, α (n) and η (n) , are adjusted according to Formulas (6) and (7).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the impact of the COVID-19 pandemic [7], when deeply analyzed, helps remap the supply chain software blueprints as SMEs became aware of the software dependency on time, accuracy, financial resources, and future growth scalability for empowering a resilient and competitive supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, there has been an increase in man-made disasters due to oversights from organisations that have had a significant humanitarian impact. Events such as the terrorist attacks of September 11th in 2001 and Hurricane Katrina in 2005 in the United States, the 2004 tsunami in Asia, the 2009 H1N1 world pandemic, the earthquakes in Chile and Haiti in 2010, the Ebola virus in West Africa between 2013 and 2016 and, more recently, the new coronavirus pandemic, beginning in 2019, and the Russian-Ukrainian war, in 2022, are all examples of disasters with long post-disaster environmental, social and economic recovery processes [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous and exogenous causes, however, had negative impacts such as disruptions and slowdowns. Because the pandemic represents one of the most severe outages in history, practitioners and researchers have been challenged to increase supply chain resilience [1][2][3][4][5]. Globally, 75% of enterprises observed SC interruptions due to transportation limitations in the wholesale distribution phases [6,7], including border restrictions as well as other restrictive policies.…”
Section: Introductionmentioning
confidence: 99%
“…These research questions reflect research gaps, identified by considering the six-step problematization methodology of [34]: (1) the domain is the disruption effect on wholesale warehouses; (2) the assumption is that the discipline of resilience engineering is nowadays uncommon in warehouse management; (3) the problematization of this last assumption confirms the opportunity to use resilience engineering since it is recognized as a successful paradigm for risky situations [35]; (4) thus, the authors assumed that resilience engineering can add knowledge to researchers and practitioners of warehouse management on how to cope with disruptive events; (5) this problem and the subsequent research questions could strongly benefit several supply chains, often hit by disruptive events (recently, a pandemic and war), thus research questions are interesting for the audience, and (6) the answers to the research questions are not obvious or absurd.…”
mentioning
confidence: 99%